Hot cross bun sign in a Peruvian patient with spinocerebellar ataxia type 2: A case report - Tantalean-Gutierrez, Lily (2023)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant inherited neurodegenerative disease, caused by an abnormal CAG trinucleotide expansion in the ATXN2 gene. SCA2 usually occurs in adulthood, with progressive ataxia associated with peripheral neuropathy, impaired eye movements, parkinsonism, and other symptoms. Auxiliary exams include biochemical tests, neuroimaging such as brain MRI, and a molecular genetic study. We describe, for the first time in the Peruvian population, the case of a middle-aged woman with a confirmed diagnosis of SCA2, whose brain MRI shows the “Hot Cross Bun Sign”.